Probing the Thermodynamic State of a Coronal Mass Ejection (CME) Up to 1 AU - Mishra, Wageesh; Wang, Yuming; Teriaca, Luca; Zhang, Jie; Chi, Yutian (Frontiers in Astronomy and Space Sciences, 2020)
Several earlier studies have attempted to estimate some of the thermodynamic properties of Coronal Mass Ejections (CMEs) either very close to the Sun or at 1 AU. In the present study, we attempt to extrapolate the internal thermodynamic properties of 2010 April 3 flux rope CME from near the Sun to 1 AU. For this purpose, we use the flux rope internal state (FRIS) model which is constrained by the kinematics of the CME. The kinematics of the CME is estimated using the STEREO/COR and HI observations in combination with drag based model (DBM) of CME propagation. Using the FRIS model, we focus on estimating the polytropic index of the CME plasma, heating/cooling rate, entropy changing rate, Lorentz force and thermal pressure force acting inside the CME. Our study finds that the polytropic index of the selected CME ranges between 1.7 and 1.9. This implies that the CME is in the heat-releasing state (i.e., entropy loss) throughout its journey from the Sun to Earth. The hindering role of Lorentz force and contributing role of thermal pressure force in governing the expansion of the CME is also identified. On comparing the estimated properties of the CME flux rope from the FRIS model with the in situ observations of the CME taken at 1 AU, we find relevant discrepancies between the results predicted by the model and the observations. We outline the approximations made in our study of probing the internal state of the CME during its heliospheric evolution and discuss the possible causes of the observed discrepancies.